Chalcopyrite / bornite heterojunction photo-Fenton catalyst and its preparation method and application

By using chalcopyrite/copperite heterojunction photofenton catalyst, the problem of low photogenerated electron utilization in the photofenton system is solved, and efficient degradation of organic pollutants is achieved, and the total organic carbon removal rate reaches more than 60%.

CN118874496BActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411127543.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-28
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The utilization rate of photogenerated electrons in the existing photofenton system is low, resulting in insufficient mineralization capacity for organic pollutants.

Method used

The chalcopyrite/cubicorite heterojunction photofenton catalyst is used, and its structure is a flower-like microsphere formed by self-assembly of hexagonal nanosheets. It has an S-shaped heterostructure. It is prepared by hydrothermal synthesis and high-temperature calcination to promote photogenerated electrons to gather on the CuFeS2 side, realizing the circulation of Fe(III)/Fe(II) and Cu(II)/Cu(I) and continuously activate H2O2.

Benefits of technology

1 mg/L-20 mg/L organic pollutants can be completely degraded within 5 minutes, and the total organic carbon removal rate can reach more than 60% in 30 minutes, which significantly improves the efficiency of photofenton degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118874496B_ABST
    Figure CN118874496B_ABST
Patent Text Reader

Abstract

The present invention discloses a chalcopyrite / bornite heterojunction photo-Fenton catalyst, a preparation method and an application thereof, comprising dissolving a copper salt and an iron salt in deionized water, stirring to obtain a uniform mixed solution; adding thiourea to deionized water and dissolving it, and then adding it to the copper-iron mixed solution and stirring it thoroughly to obtain a reaction solution; transferring the reaction solution to a polytetrafluoroethylene liner for hydrothermal reaction, cooling to obtain a reaction product; and centrifuging, washing, drying, calcining and grinding the reaction product. The catalyst of the present invention has a large amount of Cu(I) and Fe(II), can provide abundant catalytic active sites to participate in the Fenton reaction, has a strong visible light absorption capacity, can generate a large amount of photogenerated electrons, and has excellent photo-Fenton performance in degrading organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a chalcopyrite / bornite heterojunction photo-Fenton catalyst, a preparation method of the catalyst, and an application of the catalyst. Background Art

[0002] With the rapid development of the economy and society, the discharge of industrial, medical and domestic wastewater is increasing year by year. The residual refractory organic matter in these wastewaters is harmful to the human body and the ecological environment. It is urgent to take effective measures to completely remove it from the water body. As a typical advanced oxidation technology, heterogeneous Fenton technology has great advantages in the application of treating refractory organic pollutants because it can generate hydroxyl radicals (·OH) with strong oxidizing properties. However, due to the slow regeneration of the active sites of the catalyst in the oxidation system and the low effective utilization rate of hydrogen peroxide (H2O2), this technology still has the problem of insufficient mineralization ability for pollutants in practical applications. At present, copper-iron bimetallic heterogeneous catalysis can improve the activation efficiency of H2O2 to a certain extent. However, the electron transfer ability and regeneration rate of the dual reaction active centers of this type of catalyst are still not ideal, resulting in insufficient mineralization ability for organic pollutants in the Fenton reaction. Based on the photo-Fenton system developed by heterogeneous Fenton, the catalyst can generate photogenerated electrons with reducing ability under light excitation, promote the circulation of Fe(Ⅲ) / Fe(Ⅱ) and Cu(Ⅱ) / Cu(Ⅰ), and realize the effective regeneration of active sites. However, most of the current iron-based or copper-based catalysts still have the problems of high photogenerated electron-hole recombination rate and low utilization rate of photogenerated electrons. Summary of the invention

[0003] The first purpose of the present invention is to provide a chalcopyrite / bornite heterojunction photo-Fenton catalyst, which solves the problem of low utilization rate of photogenerated electrons in the existing photo-Fenton system.

[0004] The second object of the present invention is to provide a method for preparing a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0005] The third object of the present invention is to provide the application of chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0006] The first technical solution adopted by the present invention is that the chalcopyrite / bornite heterojunction photo-Fenton catalyst has a structure of flower-shaped microspheres formed by self-assembly of hexagonal nanosheets, the diameter of the microspheres is 3μm-7μm, and the side length of the nanosheets is 150nm-250nm.

[0007] The first technical solution of the present invention is also characterized in that:

[0008] The ratio of Cu(Ⅱ):Cu(Ⅰ) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:1-1:4, and the ratio of Fe(Ⅲ):Fe(Ⅱ) is 1:0.8-1:1. The chalcopyrite / bornite heterojunction photo-Fenton catalyst has an S-type heterostructure.

[0009] The second technical solution adopted by the present invention is a method for preparing a chalcopyrite / bornite heterojunction photo-Fenton catalyst, which is specifically implemented according to the following steps:

[0010] Step 1, dissolving copper salt and iron salt in deionized water, and stirring to obtain a uniform mixed solution;

[0011] Step 2, adding thiourea to deionized water to dissolve it, and then adding it to the mixed solution of step 1 and stirring it thoroughly to obtain a reaction solution;

[0012] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product;

[0013] Step 4: centrifuge, wash, dry, calcine, and then grind the reaction product obtained in step 3 into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0014] The second technical solution of the present invention is also characterized in that:

[0015] The copper salt in step 1 is one of copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron chloride, iron nitrate or iron sulfate.

[0016] In step 1, the molar ratio of copper salt to iron salt is 1:0.3-1:1, the amount of deionized water is 20 mL-50 mL, and the stirring temperature is 15° C.-30° C.

[0017] In step 2, the molar ratio of the total amount of copper salt and iron salt to thiourea is 1:2-1:8, deionized water is 20 mL-50 mL, and stirring is carried out at 15° C.-30° C. for 20 min-60 min.

[0018] In step 3, the hydrothermal reaction temperature is 140°C-200°C, and the reaction time is 10h-20h.

[0019] In step 4, the mixture is washed with anhydrous ethanol for 3-5 times and then with deionized water for 2-5 times. The freeze-drying time is 12h-24h, the calcination temperature is 400°C-800°C, and the reaction time is 2h-5h.

[0020] The third technical solution adopted by the present invention is the application of chalcopyrite / bornite heterojunction photo-Fenton catalyst in photo-Fenton degradation and removal of organic pollutants in water.

[0021] The third technical solution of the present invention is also characterized in that:

[0022] The organic pollutant is one of phenolic pollutants, drugs or dyes.

[0023] The beneficial effects of the present invention are:

[0024] The chalcopyrite / bornite (CuFeS2 / Cu5FeS4) heterojunction photo-Fenton catalyst of the present invention has a large amount of Cu (I) and Fe (II), which can provide abundant catalytic active sites to participate in the Fenton reaction; the chalcopyrite / bornite heterojunction photo-Fenton catalyst has strong visible light absorption ability and can generate a large amount of photogenerated electrons; the S-type heterostructure of the chalcopyrite / bornite heterojunction is conducive to the separation of photogenerated electron-hole pairs; the internal electric field of the chalcopyrite / bornite heterojunction can promote the directional migration of photogenerated electrons from Cu5FeS4 to CuFeS2; the photo-Fenton degradation performance of organic pollutants is excellent, and within 5 minutes, 1 mg / L-20 mg / L of organic pollutants (phenolic pollutants, drugs, dyes) can be completely degraded, and the total organic carbon removal rate can reach more than 60% in 30 minutes. The method for preparing a chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention prepares a chalcopyrite / bornite heterojunction photo-Fenton catalyst with an S-type heterostructure through two steps of hydrothermal synthesis and high-temperature calcination, thereby causing a large number of photogenerated electrons to gather on the CuFeS2 side, and the photogenerated electrons with high reducing power promote the circulation of Fe(III) / Fe(II) and Cu(II) / Cu(I), thereby realizing the continuous activation of H2O2; the preparation process is simple and controllable, the preparation cost is low, and the raw materials are cheap and easily available. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an X-ray diffraction spectrum of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention;

[0026] Figure 2 The scanning electron microscope, transmission electron microscope, high-resolution transmission electron microscope and selected area electron diffraction diagram of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention are shown;

[0027] Figure 3 This is the XPS graph of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention;

[0028] Figure 4 It is the ultraviolet-visible diffuse reflectance image of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention;

[0029] Figure 5 The photo-Fenton degradation of phenol by the chalcopyrite / bornite heterojunction photo-Fenton catalyst and CuFeS2 and Cu5FeS4 of the present invention;

[0030] Figure 6The chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention is used for photo-Fenton degradation of different pollutants;

[0031] Figure 7 It is the total organic carbon removal rate of different pollutants by the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] The preparation method of the chalcopyrite / bornite (CuFeS2 / Cu5FeS4) heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0034] Step 1, dissolving copper salt and iron salt in deionized water, and stirring to obtain a uniform mixed solution;

[0035] The copper salt in step 1 is one of copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron chloride, iron nitrate or iron sulfate;

[0036] In step 1, the molar ratio of copper salt to iron salt is 1:0.3-1:1, the amount of deionized water is 20 mL-50 mL, and the stirring temperature is 15°C-30°C;

[0037] Step 2, adding thiourea to deionized water to dissolve it, and then adding it to the mixed solution of step 1 and stirring it thoroughly to obtain a reaction solution;

[0038] The molar ratio of the total amount of copper salt and iron salt to thiourea in step 2 is 1:2-1:8, deionized water is 20 mL-50 mL, and stirring is carried out at 15° C.-30° C. for 20 min-60 min;

[0039] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product;

[0040] In step 3, the hydrothermal reaction temperature is 140°C-200°C, and the reaction time is 10h-20h;

[0041] Step 4: centrifuging, washing, drying, calcining, and then grinding the reaction product obtained in step 3 into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst;

[0042] In step 4, the mixture is washed with anhydrous ethanol for 3-5 times and then with deionized water for 2-5 times. The freeze-drying time is 12h-24h, the calcination temperature is 400°C-800°C, and the reaction time is 2h-5h.

[0043] The structure of the chalcopyrite / bornite heterojunction photo-Fenton catalyst prepared by the invention is a flower-shaped microsphere formed by self-assembly of hexagonal nanosheets, the diameter of the microsphere is 3 μm-7 μm, the side length of the nanosheet is 150 nm-250 nm, the ratio of Cu(II):Cu(I) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:1-1:4, the ratio of Fe(III):Fe(II) is 1:0.8-1:1, and the catalyst has an S-type heterostructure.

[0044] Application of chalcopyrite / bornite heterojunction photo-Fenton catalyst in photo-Fenton degradation of organic pollutants in water; the organic pollutant is one of phenolic pollutants, drugs or dyes.

[0045] Example 1

[0046] The preparation method of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0047] Step 1, adding copper sulfate and ferric sulfate to 20 mL of deionized water, stirring at a temperature of 15° C. to obtain a uniform mixed solution, wherein the molar ratio of copper sulfate to ferric sulfate is 1:0.3;

[0048] Step 2, adding thiourea to 50 mL of deionized water and stirring until dissolved, adding the mixture to the mixed solution of step 1, stirring at a temperature of 15° C. for 20 min to obtain a reaction solution, wherein the molar ratio of the total amount of copper sulfate and iron sulfate to thiourea is 1:2;

[0049] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner, subjecting the reaction solution to a hydrothermal reaction at 140° C. for 20 h, and cooling the reaction solution to obtain a reactant;

[0050] Step 4: After centrifuging the reactant obtained in step 3, wash it three times with anhydrous ethanol, then wash it twice with deionized water, freeze-dry it for 12 hours, and calcine the reactant in an argon atmosphere for 5 hours at a calcination temperature of 400° C. The calcined product is ground into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0051] The structure of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of this embodiment is a flower-shaped microsphere formed by self-assembly of hexagonal nanosheets. The diameter of the microsphere is 3 μm, and the side length of the nanosheet is 150 nm. The ratio of Cu(Ⅱ):Cu(Ⅰ) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:1, and the ratio of Fe(Ⅲ):Fe(Ⅱ) is 1:0.8.

[0052] The X-ray diffraction spectrum of the chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example is shown in Figure 1The XRD spectrum shows the (111), (200), (220) and (311) crystal planes that can characterize the characteristic diffraction peaks of CuFeS2, as well as the (321), (242), (332), (080), (253) and (084) crystal planes of Cu5FeS4.

[0053] The chalcopyrite / bornite heterojunction photo-Fenton catalyst of this embodiment was used to degrade phenol: a 300W xenon lamp (λ>420nm) was used as the excitation light source, the reaction temperature was 25°C, the concentration of phenol in the aqueous solution was 20mg / L, the concentration of the chalcopyrite / bornite heterojunction photo-Fenton catalyst in the reaction system was 200mg / L, the concentration of H2O2 in the aqueous solution was 5.0mmol / L, the mixed solution of the chalcopyrite / bornite heterojunction photo-Fenton catalyst and phenol was kept in the dark for 30min in advance until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the surface of the solution was 250mW / cm 2 After stirring for 3 minutes, the phenol degradation rate was measured to be 100%, and after stirring for 30 minutes, the total organic carbon removal rate of phenol was measured to be 98%.

[0054] The photo-Fenton degradation of phenol by the chalcopyrite / bornite heterojunction photo-Fenton catalyst and CuFeS2 and Cu5FeS4 obtained in this example is shown in FIG. Figure 5 It can be seen that the degradation rate of phenol by the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 100% within 3 minutes. Compared with the degradation effect of pure phase CuFeS2 and Cu5FeS4, the photo-Fenton degradation effect of the composite material is greatly improved.

[0055] Example 2

[0056] The preparation method of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0057] Step 1, adding copper nitrate and ferric nitrate into 30 mL of deionized water, stirring at a temperature of 20° C. to obtain a uniform mixed solution, wherein the molar ratio of copper nitrate to ferric nitrate is 1:0.7;

[0058] Step 2, adding thiourea to 40 mL of deionized water and stirring until dissolved, adding the mixture to the mixed solution of step 1, stirring at 20° C. for 30 min to obtain a reaction solution, wherein the molar ratio of the total amount of copper nitrate and ferric nitrate to thiourea is 1:4;

[0059] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner, subjecting the reaction solution to a hydrothermal reaction at 160° C. for 16 h, and cooling the reaction solution to obtain a reactant;

[0060] Step 4: After centrifuging the reactant obtained in step 3, wash it three times with anhydrous ethanol, then wash it three times with deionized water, freeze-dry it for 20 hours, and calcine the reactant in an argon atmosphere for 4 hours at a calcination temperature of 500° C. The calcined product is ground into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0061] The structure of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of this embodiment is a flower-shaped microsphere formed by self-assembly of hexagonal nanosheets. The diameter of the microsphere is 5 μm, and the side length of the nanosheet is 170 nm. The ratio of Cu(Ⅱ):Cu(Ⅰ) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:3, and the ratio of Fe(Ⅲ):Fe(Ⅱ) is 1:0.8.

[0062] The scanning electron microscope and transmission electron microscope images of the chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example are shown in Figure 2 ab, from the scanning electron micrograph 2a, it can be seen that the apparent morphology of the chalcopyrite / bornite heterojunction photo-Fenton catalyst is a flower-like microsphere structure with an average diameter of 5 μm, and these flower-like microspheres are composed of many stacked nanosheets self-assembled. From the transmission electron micrograph 2b, it can be seen that the nano-petals are formed by stacking a plurality of hexagonal nanosheets with a side length of about 170 nm up and down; the high-resolution transmission electron micrograph and selected area electron diffraction pattern of the chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example are shown in Figure 2 cd, as can be seen from the 2c high-resolution transmission electron microscopy image, two different lattice fringes can be observed, among which the lattice spacings of 0.194 and 0.305 nm correspond to the (084) crystal plane of Cu5FeS4 and the (111) crystal plane of CuFeS2, respectively. An obvious chalcopyrite / bornite heterointerface can also be observed, indicating that the chalcopyrite / bornite heterojunction structure has been successfully formed. From the 2d selected area electron diffraction image, it can be seen that the chalcopyrite / bornite heterojunction photo-Fenton catalyst has single crystal characteristics.

[0063] Chalcopyrite / bornite heterojunction photo-Fenton catalyst for the degradation of p-chlorophenol: A 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25 °C, the concentration of p-chlorophenol in the aqueous solution was 20 mg / L, the concentration of the chalcopyrite / bornite heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of H2O2 in the aqueous solution was 5.0 mmol / L, the mixed solution of the chalcopyrite / bornite heterojunction photo-Fenton catalyst and p-chlorophenol was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached, and the light source was turned on, and the irradiation of the light source per unit area on the solution surface was 250 mW / cm 2 After stirring for 5 minutes, the degradation rate of p-chlorophenol was measured to be 100%, and the total organic carbon removal rate of p-chlorophenol was measured to be 90% after stirring for 30 minutes.

[0064] Example 3

[0065] The preparation method of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0066] Step 1, adding copper chloride and ferric chloride into 40 mL of deionized water, stirring at a temperature of 25° C. to obtain a uniform mixed solution, wherein the molar ratio of copper chloride to ferric chloride is 1:0.5;

[0067] Step 2, adding thiourea to 30 mL of deionized water and stirring until dissolved, adding the mixture to the mixed solution of step 1, stirring at 25° C. for 40 min to obtain a reaction solution, wherein the molar ratio of the total amount of copper chloride and ferric chloride to thiourea is 1:6;

[0068] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner, subjecting the reaction solution to a hydrothermal reaction at 180° C. for 10 h, and cooling the reaction solution to obtain a reactant;

[0069] Step 4: After centrifuging the reactant obtained in step 3, wash it 4 times with anhydrous ethanol, then wash it 4 times with deionized water, freeze-dry it for 16 hours, and after drying, calcine it in an argon atmosphere for 3 hours at a calcination temperature of 600° C. The calcined product is ground into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0070] The structure of the chalcopyrite / bornite heterojunction photo-Fenton catalyst is a flower-shaped microsphere formed by self-assembly of hexagonal nanosheets. The diameter of the microsphere is 6 μm and the side length of the nanosheet is 200 nm. The ratio of Cu(Ⅱ):Cu(Ⅰ) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:2, and the ratio of Fe(Ⅲ):Fe(Ⅱ) is 1:0.9.

[0071] The XPS spectra of Cu and Fe elements of the chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example before and after use are shown in Figure 3 It can be seen that the chalcopyrite / bornite heterojunction photo-Fenton catalyst has a large amount of Cu(Ⅰ) and Fe(Ⅱ), which can provide abundant active sites to participate in the Fenton reaction.

[0072] The chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example was used to degrade sulfamethoxazole: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of sulfamethoxazole in the aqueous solution was 20 mg / L, the concentration of the chalcopyrite / bornite heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of H2O2 in the aqueous solution was 5.0 mmol / L, the mixed solution of the chalcopyrite / bornite heterojunction photo-Fenton catalyst and sulfamethoxazole was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the surface of the solution was 250 mW / cm 2After stirring for 4 minutes, the degradation rate of sulfamethoxazole was measured to be 100%, and the total organic carbon removal rate of sulfamethoxazole was measured to be 78% after stirring for 30 minutes.

[0073] Example 4

[0074] The preparation method of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention is specifically implemented according to the following steps:

[0075] Step 1, adding copper chloride and ferric chloride into 50 mL of deionized water, stirring at a temperature of 30° C. to obtain a uniform mixed solution, wherein the molar ratio of copper chloride to ferric chloride is 1:1;

[0076] Step 2, adding thiourea to 20 mL of deionized water and stirring until dissolved, adding the mixture to the mixed solution of step 1, stirring at 30° C. for 60 min to obtain a reaction solution, wherein the molar ratio of the total amount of copper chloride and ferric chloride to thiourea is 1:8;

[0077] Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner, subjecting the reaction solution to a hydrothermal reaction at 200° C. for 14 h, and cooling the reaction solution to obtain a reactant;

[0078] Step 4: After centrifuging the reactant obtained in step 3, wash it with anhydrous ethanol for 5 times, then wash it with deionized water for 5 times, freeze-dry it for 24 hours, and calcine the reactant in an argon atmosphere for 2 hours at a calcination temperature of 800° C. The calcined product is ground into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

[0079] The structure of the chalcopyrite / bornite heterojunction photo-Fenton catalyst of this embodiment is a flower-shaped microsphere formed by self-assembly of hexagonal nanosheets. The diameter of the microsphere is 7 μm, and the side length of the nanosheet is 250 nm. The ratio of Cu(Ⅱ):Cu(Ⅰ) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:4, and the ratio of Fe(Ⅲ):Fe(Ⅱ) is 1:1.

[0080] The chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example was subjected to ultraviolet-visible diffuse reflectance test. Figure 4 , it can be seen that the chalcopyrite / bornite heterojunction has a strong light absorption ability in the range of 200nm-800nm.

[0081] The chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in this example was used to degrade methylene blue: a 300 W xenon lamp (λ>420 nm) was used as the excitation light source, the reaction temperature was 25° C., the concentration of methylene blue in the aqueous solution was 20 mg / L, the concentration of the chalcopyrite / bornite heterojunction photo-Fenton catalyst in the reaction system was 200 mg / L, the concentration of H2O2 in the aqueous solution was 5.0 mmol / L, the mixed solution of the chalcopyrite / bornite heterojunction photo-Fenton catalyst and methylene blue was kept in the dark for 30 min until the adsorption-desorption equilibrium was reached, the light source was turned on, and the irradiation amount of the light source per unit area on the surface of the solution was 250 mW / cm 2 After stirring for 5 minutes, the degradation rate of methylene blue was measured to be 100%, and the total organic carbon removal rate of methylene blue was measured to be 65% after stirring for 30 minutes.

[0082] The degradation effects of the chalcopyrite / bornite heterojunction photo-Fenton catalysts obtained in Examples 1-4 on phenolic compounds, drugs and dyes are shown in Table 1. Figure 6 It can be seen that the degradation rate of phenol, p-chlorophenol, sulfamethoxazole and methylene blue by the chalcopyrite / bornite heterojunction photo-Fenton catalyst can reach 100% within 5 minutes.

[0083] The total organic carbon removal rate of phenolic compounds, drugs and dyes by the chalcopyrite / bornite heterojunction photo-Fenton catalyst obtained in Examples 1-4 is shown in FIG. Figure 7 It can be seen that the total organic carbon removal efficiency of chalcopyrite / bornite heterojunction photo-Fenton catalyst for phenol is 98% in 30 min, the total organic carbon removal efficiency for p-chlorophenol is 90%, the total organic carbon removal efficiency for sulfamethoxazole is 78%, and the total organic carbon removal efficiency for methylene blue is 65%.

[0084] Through the above methods, the chalcopyrite / bornite heterojunction photo-Fenton catalyst of the present invention has a large amount of Cu (I) and Fe (II), which can provide abundant catalytic active sites to participate in the Fenton reaction; the chalcopyrite / bornite heterojunction photo-Fenton catalyst has strong visible light absorption ability and can generate a large number of photogenerated electrons; the S-type heterostructure of the chalcopyrite / bornite heterojunction is conducive to the separation of photogenerated electron-hole pairs; the internal electric field of the chalcopyrite / bornite heterojunction can promote the directional migration of photogenerated electrons from Cu5FeS4 to CuFeS2; the photo-Fenton degradation performance of organic pollutants is excellent, and within 5 minutes, 1 mg / L-20 mg / L of organic pollutants (phenolic pollutants, drugs, dyes) can be completely degraded, and the total organic carbon removal rate can reach more than 60% in 30 minutes. The chalcopyrite / bornite heterojunction photo-Fenton catalyst preparation method of the present invention prepares the chalcopyrite / bornite heterojunction photo-Fenton catalyst with an S-type heterostructure through two steps of hydrothermal synthesis and high-temperature calcination, so that a large number of photogenerated electrons are caused to gather on the CuFeS2 side, and the photogenerated electrons with high reducing power promote the circulation of Fe(III) / Fe(II) and Cu(II) / Cu(I), thereby realizing the continuous activation of H2O2; the preparation process is simple and controllable, the preparation cost is low, and the raw materials are cheap and easily available.

Claims

1. Chalcopyrite / bornite heterojunction photo-Fenton catalyst, characterized in that: The structure is a flower-like microsphere formed by self-assembly of hexagonal nanosheets, the diameter of the microsphere is 3µm-7µm, and the side length of the nanosheet is 150nm-250nm; The ratio of Cu(II):Cu(I) in the chalcopyrite / bornite heterojunction photo-Fenton catalyst is 1:1-1:4, the ratio of Fe(III):Fe(II) is 1:0.8-1:1, and the chalcopyrite / bornite heterojunction photo-Fenton catalyst has an S-type heterostructure.

2. A method for preparing a chalcopyrite / bornite heterojunction photo-Fenton catalyst, characterized in that: Follow the steps below to implement it: Step 1, dissolving copper salt and iron salt in deionized water, and stirring to obtain a uniform mixed solution; Step 2, adding thiourea to deionized water to dissolve it, and then adding it to the mixed solution of step 1 and stirring it thoroughly to obtain a reaction solution; Step 3, transferring the reaction solution obtained in step 2 to a polytetrafluoroethylene liner for hydrothermal reaction, and cooling to obtain a reaction product; Step 4: centrifuge, wash, dry, calcine, and then grind the reaction product obtained in step 3 into powder to obtain a chalcopyrite / bornite heterojunction photo-Fenton catalyst.

3. The method for preparing the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 2, characterized in that: The copper salt in step 1 is one of copper chloride, copper nitrate or copper sulfate, and the iron salt is one of iron chloride, iron nitrate or iron sulfate.

4. The method for preparing the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 2, characterized in that: In the step 1, the molar ratio of the copper salt to the iron salt is 1:0.3-1:1, the amount of deionized water is 20 mL-50 mL, and the stirring temperature is 15° C.-30° C.

5. The method for preparing the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 2, characterized in that: In the step 2, the molar ratio of the total amount of copper salt and iron salt to thiourea is 1:2-1:8, deionized water is 20 mL-50 mL, and stirring is carried out at 15° C.-30° C. for 20 min-60 min.

6. The method for preparing the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 2, characterized in that: In step 3, the hydrothermal reaction temperature is 140° C.-200° C., and the reaction time is 10 h-20 h.

7. The method for preparing the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 2, characterized in that: In step 4, the mixture is washed with anhydrous ethanol for 3-5 times and then with deionized water for 2-5 times. The freeze drying time is 12h-24h, the calcination temperature is 400°C-800°C, and the reaction time is 2h-5h.

8. Use of the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 1 in photo-Fenton degradation to remove organic pollutants in water.

9. Use of the chalcopyrite / bornite heterojunction photo-Fenton catalyst according to claim 8 in photo-Fenton degradation to remove organic pollutants in water, wherein the organic pollutant is one of phenolic pollutants, drugs or dyes.

Citation Information

Patent Citations

  • Solid-state catalysts for low or moderate temperature leach applications and methods thereof

    CA3111166A1

  • Method for desulphurization of copper sulfur ore

    CN101481806A